2003
DOI: 10.1073/pnas.2033520100
|View full text |Cite
|
Sign up to set email alerts
|

Redefining cholesterol's role in the mechanism of the cholesterol-dependent cytolysins

Abstract: The cholesterol-dependent cytolysins (CDCs) constitute a large family of pore-forming toxins that function exclusively on cholesterol-containing membranes. A detailed analysis of the various stages in the cytolytic mechanism of three members of the CDC family revealed that significant depletion of cholesterol from the erythrocyte membrane stalls these toxins in the prepore complex. Therefore, the depletion of membrane cholesterol prevents the insertion of the transmembrane ␤-barrel and pore formation. These un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
193
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(205 citation statements)
references
References 41 publications
8
193
2
2
Order By: Relevance
“…Although inhibition of toxin A-induced 86 Rb ϩ efflux was complete after cholesterol depletion by methyl-␤-cyclodextrin, it is difficult to discriminate between a "specific" effect of cholesterol in membrane insertion from a modifying effect of cholesterol depending on increase in membrane fluidity and/or lateral segregation of lipids and formation of microdomains. Besides maintaining the membrane fluidity, cholesterol facilitates the conversion of lamellar lipid structure to inverted hexagonal structures (61), which may have a facilitating role in insertion of transmembrane peptide structures (62). Whether cholesterol directly influences C. difficile toxin activity, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although inhibition of toxin A-induced 86 Rb ϩ efflux was complete after cholesterol depletion by methyl-␤-cyclodextrin, it is difficult to discriminate between a "specific" effect of cholesterol in membrane insertion from a modifying effect of cholesterol depending on increase in membrane fluidity and/or lateral segregation of lipids and formation of microdomains. Besides maintaining the membrane fluidity, cholesterol facilitates the conversion of lamellar lipid structure to inverted hexagonal structures (61), which may have a facilitating role in insertion of transmembrane peptide structures (62). Whether cholesterol directly influences C. difficile toxin activity, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, SipB and IpaB might form pores similar to cholesterol-dependent cytolysins. It remains to be determined whether cholesterol only acts as a translocator receptor or is also involved in circular oligomerization of monomers and penetration of the pre-pore into the membrane, as has been found for cholesterol-dependent cytolysins (Giddings et al, 2003).…”
Section: Type III Secretion Systemmentioning
confidence: 97%
“…However, cholesterol was found to play a more important role in insertion of the pre-pore β-barrel than in being a receptor for CDCs. Indeed, depletion of membrane cholesterol prevents pore formation by streptolysin O and intermedilysin, other CDC members from S. pyogenes and Streptococcus intermedius respectively, but does not greatly impair the binding of PFO (Giddings et al, 2003). CDCs exhibit a novel mode of action in which the toxin receptor has multiple roles in binding, pore formation and stabilization.…”
Section: Lipids and Pfts (Pore-forming Toxins)mentioning
confidence: 99%
“…ILY was active only on human cells (20), a feature seemingly inconsistent with the "cholesterol as receptor" paradigm. Giddings et al subsequently showed that ILY used human CD59 (hCD59) as its membrane receptor (21), but pore formation by ILY still required cholesterol (22). This enigma was partially resolved by Soltani et al (23), who showed that ILY loops L1-L3 underwent a cholesterol-dependent membrane insertion after ILY bound to hCD59.…”
mentioning
confidence: 99%